UCP2 silencing restrains leukemia cell proliferation through glutamine metabolic remodeling - Sancerni, Tiphaine; Renoult, Ophélie; Luby, Angèle; Caradeuc, Cédric; Lenoir, Véronique; Croyal, Mikael; Ransy, Céline; Aguilar, Esther; Postic, Catherine; Bertho, Gildas; Dentin, Renaud; Prip-Buus, Carina; et al. (Frontiers in Immunology, 2022)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic malignancy derived from early T cell progenitors. Since relapsed T-ALL is associated with a poor prognosis improving initial treatment of patients is essential to avoid resistant selection of T-ALL. During initiation, development, metastasis and even in response to chemotherapy, tumor cells face strong metabolic challenges. In this study, we identify mitochondrial UnCoupling Protein 2 (UCP2) as a tricarboxylic acid (TCA) cycle metabolite transporter controlling glutamine metabolism associated with T-ALL cell proliferation. In T-ALL cell lines, we show that UCP2 expression is controlled by glutamine metabolism and is essential to enable appropriate use of glutamine for bioenergetics. Our data support the concept that the metabolite export function of UCP2 enables optimal function of the TCA cycle, ensuring appropriate oxidation of energy substrates thereby providing building blocks for cell growth and proliferation. In leukemia cells that rely on oxidative metabolism, UCP2 silencing alters proliferation by rewiring their cellular metabolism to glycolysis. Therefore, interfering with UCP2 function can be considered as an interesting strategy to decrease metabolic efficiency and proliferation rate of leukemia cells.